Pemanfaatan Media Digital Pop Up Book dalam Pembelajaran Sejarah Khlufaur Rasyidin di Kelas 6 SD - Sallsa Nurfarida; Dhea Amanda Putri; Azmi Hofifah; Ani Nur Aeni (Departement of Mathematics Education, 2023)
The research entitled The Use of Pop Up Book Digital Media in Learning History of Khulfaur Rasyidin in Grade 6 SD. The purpose of this study was to analyze the use of digital pop up book media on the effectiveness of learning the history of the Rashidun Khulafaur history. This study used the Design and Development (D&D) method by developing the ADDIE development model. Based on expert reviews from media experts, material experts and students at SDN Sukamaju digital learning media pop up books have an average pressure that shows a value of 83% with an interpretation of